If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -3 = -1(x + 1) Reorder the terms: -3 + y = -1(x + 1) Reorder the terms: -3 + y = -1(1 + x) -3 + y = (1 * -1 + x * -1) -3 + y = (-1 + -1x) Solving -3 + y = -1 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + y = -1 + 3 + -1x Combine like terms: -3 + 3 = 0 0 + y = -1 + 3 + -1x y = -1 + 3 + -1x Combine like terms: -1 + 3 = 2 y = 2 + -1x Simplifying y = 2 + -1x
| 3-(x+7)=3(2x+3) | | 86.010*LOG(32)-70.041*LOG(72)+36.76= | | 8x9/59 | | (5x/2)-X=(x/6)-(16/3) | | 10-5x=35 | | y=(-2+1)(-2+1)-4 | | 4-(3x-5)=6+2(3x-5) | | x=6-2y | | 5x+9y=23 | | 3x/5+6=24 | | 2/9+2/15 | | 3.749/10000 | | 135/225 | | 288=2x+18x | | 4x/12=4/6 | | 20r=4 | | -5y+9x=7 | | 18x+288=x | | 10/3/5/7 | | 3(2m-5)+14=44+9m | | a/a-7=-5/a-3 | | 2x+40+4x-40=360 | | 3(2+-5)+4t= | | 8/9=4/5k | | 7y+y=56 | | 3y+5/3-y-9/4=1/4+8-y/2 | | 2*x+32= | | 3(4-2y)=15 | | t/7=-5 | | 6x^2+36x=-54 | | 8a-2(3+4a)= | | 10y+30=3+15y |